In situ anchoring iron oxide nanoparticles onto polyester/disperse dye for production of multifunctional fabrics - Tarek Abou Elmaaty; Sherif Abd Elsalam; Shaimaa Helal; Shereen A. Abdeldayem (Fashion and Textiles, 2023)
Abstract Medical textiles, including surgical gowns, masks are used as obstacles to prevent the risk of infection for both doctor and patient. The widespread of bacteria and viruses, e.g. chronic hepatitis B, hepatitis C and currently Covid-19 viruses in the patient population is very common. In this work, multifunctional eco-friendly polyester fabrics have been produced by in situ impregnation of 2-((E)-(2-(2,4-dinitrophenyl)hydrazono)methyl)-4-((E)-phenyldiazenyl)phenol disperse dye onto magnetic iron oxide nanoparticles. The technique endowed polyester fabrics with a new color as well as magnetic and antibacterial functionalities. The colored magnetic nanoparticles showed high affinity toward fabrics. Besides, the unbound dye could be easily collected from wastewater by a magnet, significantly facilitate the wastewater treatment. The treated fabrics were analyzed by energy dispersive X-ray spectroscopy, scanning electron microscopy, X-ray diffraction and vibrating sample magnetometry. Colorimetric values, tensile properties and fastness of the composite fabrics were also measured. The tensile properties of the composite were increased after functionalization. The wettability features of the fabric were investigated and showed a significant improvement. Also, the toxicity of the resulted fabric was exhibited low toxicity against wi-38 cell line. These results indicate the potentiality of the suggested technique in producing multifunctional fabrics with various applications, especially as medical textiles.